Bistable molecules development and Si surface grafting: two chemical tools used for the fabrication of hybrid molecule/Si CMOS component. (22nd February 2010) - Duclairoir, Florence; Dubois, Lionel; Calborean, Adrian; Fateeva, Alexandra; Fleury, Benoit; Kalaiselvan, Anbarasan; Marchon, Jean-Claude; Maldivi, Pascale; Billon, Martial; Bidan, Gerard; Salvo, Barbara; Delapierre, Guillaume; et al.
For the past ten years, there has been considerable interest dedicated to the miniaturisation of CMOS devices. The research axes followed to obtain scalable devices are numerous as the possibilities offered by both technological (top-down) and new (bottom-up) approaches are studied. Concerning the latter approach molecular electronics is a growing field of interest. Notably, the fabrication of hybrid molecule/Si structures paves the way for development of devices with electrical performances that can be tuned thanks to the molecular properties initially targeted. Here we present the recent results obtained in the two approaches we follow in order to develop new hybrid molecule/Si memory elements. The first axis focuses on the development of specific molecules that could allow a fine tuning of the memory retention characteristic. The second axis deals with the integration of redox molecules inside capacitive cells and the study of their electrical properties. The capacitance of such components clearly shows that an effect of charge transfer is observed only when redox active molecules (porphyrins) are grafted on Si.